Learning Management Based on Information and Communication Technology in Improving Student Learning Outcomes - Sri Nurabdiah Pratiwi (RIRAI Publisher, 2023)
Information and communication technology (ICT) is strongly tied to learning in the digital age, thus teachers and students must be able to use digital tools in all learning processes. It is evident that information technology significantly contributes to pupils' increased creativity in both large cities and rural towns. To fulfil all educational goals in general and school goals in particular, ICT application for increasing learning needs to be planned and evaluated according to the needs of students, teachers, and the school itself. According to the problem's issue, a literature review was used to collect data for this study. The study's findings indicate that planning is done to make the most of the ICT-based learning process. Planning starts by examining the requirements and circumstances of the school, including all of its strengths and weaknesses, and then evaluation is done to determine the ICT's dependability and strengths and weaknesses. For ICT to be used in the learning process, there must be a reliable internet connection. If there are issues with the learning process, the root reason may be quickly determined, and the primary solution is sought right away. According to the study's findings, ICT-based learning management can significantly enhance students' ability to learn to contemporary needs and the Merdeka curriculum.